Desarrollo de habilidades de comprensión lectora en inglés –como lengua extranjera- en estudiantes de quinto de primaria (2017)
This article describes the research process whose objective was developing reading comprehension skills in English - as a foreign language - in fifth grade students from a public school in the municipality of Cartago (V), Colombia. This proposal was based on the contributions of Solé (1998); Jouini (2005); Van Dijk & Kintsch (1983); and Cummins (1983); among others, from the perspective of interactive reading that understands textual comprehension as a process of interaction between the reader and the text. The type of study was qualitative based on a case study approach to analyse how students developed comprehension reading skills in English. The instrument of analysis was a didactic unit entitled -Healthy food- composed by an instrument of previous ideas applied as pre-test and post-test and four sequences containing eight questionnaires that supported the analysis of the information.